2016
DOI: 10.1074/jbc.m115.693911
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Canonical (TRPC)/Orai1-dependent Store-operated Ca2+ Channels

Abstract: Store-operated Ca2؉ entry (SOCE) has emerged as an important mechanism in cardiac pathology. However, the signals that up-regulate SOCE in the heart remain unexplored. Clinical trials have emphasized the beneficial role of mineralocorticoid receptor (MR) signaling blockade in heart failure and associated arrhythmias. Accumulated evidence suggests that the mineralocorticoid hormone aldosterone, through activation of its receptor, MR, might be a key regulator of Ca 2؉ influx in cardiomyocytes. We thus assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 75 publications
4
68
1
Order By: Relevance
“…Due to the lack of information regarding the precise inhibitory effect of BTP2, our data only propose TRPC4 channels as down-stream targets of Ang II stimulation, but do not reveal the precise mode of channel activation. A recent study suggests that TRPC1, 4 and 5 comprise SOC channels in association with ORAI1 that are downstream targets of aldosterone stimulation in NRCs [34]. Further studies are necessary to examine whether such a miscellaneous constellation could also mediate Ca 2+ responses after Ang II stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of information regarding the precise inhibitory effect of BTP2, our data only propose TRPC4 channels as down-stream targets of Ang II stimulation, but do not reveal the precise mode of channel activation. A recent study suggests that TRPC1, 4 and 5 comprise SOC channels in association with ORAI1 that are downstream targets of aldosterone stimulation in NRCs [34]. Further studies are necessary to examine whether such a miscellaneous constellation could also mediate Ca 2+ responses after Ang II stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that rat aorta treated with aldosterone (10 nM for 24 h) did not reveal changes in the expression of TRPC1, C3, C4, C5, and C6 [19]. Altogether, these studies suggest a concentration-dependent increase of TRPC channels, since we have previously demonstrated an upregulation of TRPC1, C4, and C5 in cardiomyocytes upon aldosterone concentrations higher than 100 nM [43]. Moreover, one of the features of metabolic syndrome is the elevated plasma aldosterone level [116], which has been associated with increased TRPC1 and TRPC6 expression in coronary arteries compared to lean pigs [32].…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 68%
“…Moreover, it has been showed that the MR transcriptional activity is blunted by MR antagonists, and actinomycin D (a transcriptional inhibitor) supporting an MR-dependent effect of Aldo in vessels [16,19,30,41]. Furthermore, an increasing body of evidence has underlined the ability of MR to modulate the expression of ion channels in several vascular beds, unveiling the role of MR in vascular physiology and pathology [19,30,42,43].…”
Section: Genomic Effects Of Aldosterone In Vesselsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under suppressed voltage-dependent K + , Na + and Ca 2+ currents, 2-APB (40 μM) inhibited whole-cell membrane current in ground squirrel cardiomyocytes (Fig 5A). Subtraction of the currents measured in the presence of 2-APB from control records revealed a non-selective 2-APB-sensitive current component with reversal potential slightly more negative than 0 mV (E r = -11.7 ± 5.2 mV, n = 3), which is typical for non-selective SOCE measured in heterologous expression systems [59,60] or in adult cardiomyocytes [45,61]. However, in ground squirrel cardiomyocytes 2-APB-sensitive currents were detected without a pretreatment aimed at depleting intracellular Ca 2+ stores, indicating that the detected current could be induced by certain Trpc-Orai1-Stim1 channels capable of operating in store-independent mode [36,40,62].…”
Section: Resultsmentioning
confidence: 99%